Jointly structuring triadic spaces of meaning and action: book sharing from 3 months on - Rossmanith, Nicole; Costall, Alan; Reichelt, Andreas F.; López, Beatriz; Reddy, Vasudevi (Frontiers in Psychology, 2014)
This study explores the emergence of triadic interactions through the example of book sharing. As part of a naturalistic study, 10 infants were visited in their homes from 3-12 months. We report that (1) book sharing as a form of infant-caregiver-object interaction occurred from as early as 3 months. Using qualitative video analysis at a micro-level adapting methodologies from conversation and interaction analysis, we demonstrate that caregivers and infants practiced book sharing in a highly co-ordinated way, with caregivers carving out interaction units and shaping actions into action arcs and infants actively participating and co-ordinating their attention between mother and object from the beginning. We also (2) sketch a developmental trajectory of book sharing over the first year and show that the quality and dynamics of book sharing interactions underwent considerable change as the ecological situation was transformed in parallel with the infants' development of attention and motor skills. Social book sharing interactions reached an early peak at 6 months with the infants becoming more active in the coordination of attention between caregiver and book. From 7-9 months, the infants shifted their interest largely to solitary object exploration, in parallel with newly emerging postural and object manipulation skills, disrupting the social coordination and the cultural frame of book sharing. In the period from 9-12 months, social book interactions resurfaced, as infants began to effectively integrate object actions within the socially shared activity. In conclusion, to fully understand the development and qualities of triadic cultural activities such as book sharing, we need to look especially at the hitherto overlooked early period from 4-6 months, and investigate how shared spaces of meaning and action are structured together in and through interaction, creating the substrate for continuing cooperation and cultural learning.